Are bone turnover markers associated with volumetric bone density, size, and strength in older men and women? The AGES–Reykjavik study. Issue 5 (May 2016) - Marques, E.; Gudnason, V.; Sigurdsson, G.; Lang, T.; Johannesdottir, F.; Siggeirsdottir, K.; Launer, L.; Eiriksdottir, G.; Harris, T.
Abstract Summary Association between serum bone formation and resorption markers and bone mineral, structural, and strength variables derived from quantitative computed tomography (QCT) in a population-based cohort of 1745 older adults was assessed. The association was weak for lumbar spine and femoral neck areal and volumetric bone mineral density. Introduction The aim of this study was to examine the relationship between levels of bone turnover markers (BTMs; osteocalcin (OC), C-terminal cross-linking telopeptide of type I collagen (CTX), and procollagen type 1N propeptide (P1NP)) and quantitative computed tomography (QCT)-derived bone density, geometry, and strength indices in the lumbar spine and femoral neck (FN). Methods A total of 1745 older individuals (773 men and 972 women, aged 66–92 years) from the Age, Gene/Environment Susceptibility (AGES)–Reykjavik cohort were studied. QCT was performed in the lumbar spine and hip to estimate volumetric trabecular, cortical, and integral bone mineral density (BMD), areal BMD, bone geometry, and bone strength indices. Association between BTMs and QCT variables were explored using multivariable linear regression. Results Major findings showed that all BMD measures, FN cortical index, and compressive strength had a low negative correlation with the BTM levels in both men and women. Correlations between BTMs and bone size parameters were minimal or not significant. No associations were found between BTMs and vertebral cross-sectional area in women. BTMs alone accounted for only a relatively small percentage of the bone parameter variance (1–10 %). Conclusion Serum CTX, OC, and P1NP were weakly correlated with lumbar spine and FN areal and volumetric BMD and strength measures. Most of the bone size indices were not associated with BTMs; thus, the selected bone remodeling markers do not reflect periosteal bone formation. These results confirmed the limited ability of the most sensitive established BTMs to predict bone structural integrity in older adults.